Impacts of urbanization, LULC, LST, and NDVI changes on the static water table with possible solutions and water policy discussions: A case from Islamabad, Pakistan - Sohail, Muhammad Tayyab; Manzoor, Zaira; Ehsan, Muhsan; Al-Ansari, Nadhir; Khan, Muhammad Bashir; Shafi, Ahsan; Ullah, Jar; Hussain, Asrar; Raza, Danish; Usman, Umar; Akbar, Sameem; Elbeltagi, Ahmed (Frontiers in Environmental Science, 2023)
Rapid urbanization, coupled with land use land cover changes (LULC), has caused stress on freshwater resources around the globe. As in the case of Islamabad, the capital of Pakistan, the population has increased significantly, creating a deficit of natural resources and affecting the environment adversely. Therefore, the purpose of this study is to examine the effects of urbanization and LULC on the decline of the static water table in Islamabad. It also seeks to analyze water policy issues in order to achieve sustainable water resource development. The excessive pumping of the existing groundwater has exceeded the safe limit, which is justified by the constantly growing population. However, the changes in the LULC of the study area have turned many green pastures into barren land. Our research data were obtained from the Capital Development Authority (CDA), Pakistan Meteorological Department (PMD), and Landsat Satellite images. After analyzing PMD and CDA data for the last 20 years (2000–2020), the results were interpreted using Arc GIS. It has been observed that the Normalized Difference Vegetation Index (NDVI) value increases as the Land Surface Temperature (LST) decreases. Therefore, the overall observation is a decreasing trend in Islamabad temperatures due to the increased vegetation in the study area during the period of 2000–2020. It was observed that there has been a considerable drop in water levels due to over-pumping in a few areas. It is primarily associated with the increasing population of the capital in the last 2 decades. This study uses a survey to explore the potential locations for check dams to enhance and recharge the groundwater aquifers in the capital, Islamabad. It suggests catchment areas throughout the Margalla Hills along with different localities, such as Rumli Village, Trail 5, and Shahdara.